2016
DOI: 10.1155/2016/5086414
|View full text |Cite
|
Sign up to set email alerts
|

Extrapedicular Infiltration Anesthesia as an Improved Method of Local Anesthesia for Unipedicular Percutaneous Vertebroplasty or Percutaneous Kyphoplasty

Abstract: Aim. This report introduces extrapedicular infiltration anesthesia as an improved method of local anesthesia for unipedicular percutaneous vertebroplasty or percutaneous kyphoplasty. Method. From March 2015 to March 2016, 44 patients (11 males and 33 females) with osteoporotic vertebral compression fractures with a mean age of 71.4 ± 8.8 years (range: 60 to 89) received percutaneous vertebroplasty or percutaneous kyphoplasty. 24 patients were managed with conventional local infiltration anesthesia (CLIA) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…To minimize the effect on the general situation of elderly patients, PKP under local anesthesia is an effective method for treating OVFs [10][11][12]. Liu et al reported that local anesthesia for single vertebra PKP surgery can effectively relieve pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the effect on the general situation of elderly patients, PKP under local anesthesia is an effective method for treating OVFs [10][11][12]. Liu et al reported that local anesthesia for single vertebra PKP surgery can effectively relieve pain.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons can directly assess whether a spinal cord nerve injury occurs while the patient is awake. Moreover, patients who receive local anesthesia do not need postoperative resuscitation and can get out of bed early, which is conducive to postoperative rehabilitation [10][11][12]. However, when patients with m-OVFs receive local anesthesia, uoroscopy time often has to be increased, the operative time has to be extended, or the operation has to be terminated because of body posture-related discomfort, excessive local anesthetic drugs, the toxic reaction of bone cement, and abrupt uctuation of vital signs.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous kyphoplasty (PKP) is a good treatment for patients of VCF who cannot bear the pain or do not get well from conservative treatment [6]. Nowadays, both local anesthesia and general anesthesia are widely used in the PKP process [7][8][9][10][11][12]. However, the controversy about the best type of anesthesia for PKP has never been stopped.…”
Section: Introductionmentioning
confidence: 99%
“…In the puncture technique of the extrapedicular approach, the puncture needle must cling to the lateral side of the upper articular process and the upper edge of the basal transverse process and penetrate the vertebral body at the junction between the lateral side of the pedicle and the posterolateral side of the vertebral body. [5] However, the lumbar artery (LA) is distributed on the posterolateral side of the vertebral body, and the intersegmental branch passes through the lateral side of the pedicle that comes from the upper segmental LA; therefore, the extrapedicular approach carries a risk of LA injury. [69] Heo et al .…”
Section: Introductionmentioning
confidence: 99%